Design and Evaluation of User Interface Usability for Junior High School Websites in West Papua Province Using System Usability Scale - Podajow, Devid Riswandy; Inan, Dedi I.; Juita, Ratna; Sanglise, Marlinda; Subay, Natasya Yusinta (STMIK Banjarbaru, 2024)
The primary emphasis of this study lies in utilizing the System Usability Scale (SUS) method to assess the User Interface (UI) and User Experience (UX) design. The objective is to enhance the accessibility of information at SMP YPK 01 Manokwari, a school currently facing challenges due to the absence of an official website. By concentrating on designing a user-friendly UI, this research aims to facilitate users' ease in accessing information. Through the SUS method, the UI/UX design is thoroughly evaluated to ensure optimal usability. Findings from the questionnaire, which involved 33 respondents, revealed a commendable SUS score of 83.26, categorizing the tested UI/UX design as